A Study on the Relationship among Physical Environment of Festivals, Perceived Value, Participation Satisfaction, and Festival Image - Cheon, Yong-Soo (International Review of Management and Marketing, 2016)
This study was conducted by the researcher from April 4th to May 29th, 2016 on the participants of Chuncheon International Mime Festival, Yangpyeong Strawberry Festival, Yeouido Cherry Blossom Festival, and Icheon Ceramics Festival in Korea. A total of 200 copies of surveys were distributed and of them, 180 copies were used for the final analysis. This study aims verify a number of questions including how the physical environment of a festival influences the perceived value and participation satisfaction, what effects does the perceived value have on participation satisfaction and festival image, and how the participation satisfaction affects the festival image. Thus, physical environment is composed of five factors including design/atmosphere, convenience, information availability, festival program, and accessibility. Whereas perceived value, participation satisfaction, and festival image are all constructed as single dimensions. According to the analysis, first, the design/atmosphere and accessibility factors within the physical environment of a festival do have statistically significant effects on the perceived value and participation satisfaction, while factors of convenience, information availability, and festival program do not exert statistically significant influences. Second, perceived value does have statistically significant effects on participation satisfaction and festival image. Third, participation satisfaction also has statistically significant impacts on festival image. Keywords: Physical environment, perceived value, participation satisfaction, festival image JEL Classification: Z32